The Prevalence of S. Aureus Nasal Colonisation and its Antibiotic Sensitivity Pattern amongst Primary School Pupils - Assafi, Mahde S.; Polse, Reem F.; Hussein, Nawfal R.; Haji, Ahmed H.; Issa, Araz R. (Science Journal of University of Zakho, 2017)
Staphylococcus aureus is one of the most adaptable human pathogens. Nasal Staphylococcus aureus is the main cause of community-associated staphylococcal infections. This project aimed to study the prevalence of nasal carriage of Staphylococcus aureus and community-associated methicillin resistant Staphylococcus aureus (CA-MRSA) and evaluate their antibiotic susceptibility tests among primary school children at Zakho city, Kurdistan region, Iraq. Nasal swabs were taken from a total of 300 primary school pupils aged 8-12 years. Collected nasal swabs were processed according to the standard bacteriological culture and isolates were identified using mannitol fermentation, Gram stain, catalase test and coagulase test. Antimicrobial susceptibility test was carried out on Muller-Hinton agar (MHA) to determine the susceptibility of S. aureus and CA-MRSA towards antibiotics. 30% (90/300) of the primary school children carried S. aureus. The nasal carriage of MRSA was 4% (12/300) among participants. All MRSA isolates were sensitive to vancomycin, doxycycline, amikacin and ciprofloxacin. This study showed that the incidence of S. aureus and CA-MRSA is comparable with reports from elsewhere. Measures are needed to keep the emergence and transmission of these pathogens to a lowest. Antimicrobial susceptibility testing of all S. aureus isolates is crucial for treatment of MRSA. Further studies are required to detect the risk factors of the acquisition of MRSA.